2023
DOI: 10.3390/plants12020276
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals the Interaction of Sugar and Hormone Metabolism Involved in the Root Hair Morphogenesis of the Endangered Fir Abies beshanzuensis

Abstract: Abies beshanzuensis, an extremely rare and critically endangered plant with only three wild adult trees globally, is strongly mycorrhizal-dependent, leading to difficulties in protection and artificial breeding without symbiosis. Root hair morphogenesis plays an important role in the survival of mycorrhizal symbionts. Due to the lack of an effective genome and transcriptome of A. beshanzuensis, the molecular signals involved in the root hair development remain unknown, which hinders its endangered mechanism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…RNA extraction and reverse transcription were performed as described by Liu et al . (2023). PP2A served as the reference gene (Liu et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…RNA extraction and reverse transcription were performed as described by Liu et al . (2023). PP2A served as the reference gene (Liu et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The SUS pathway, which is involved in sucrose degradation, was shown to partly compensate for energy restriction in tomato roots (Shi et al ., 2008). In our previous study, we found that AbSUSs were significantly differentially expressed between radicles with and those without root hairs in Abies beshanzuensis , suggesting that they regulate root hair development (Liu et al ., 2023). The regulatory role of SUSs in root hair morphogenesis is complex and is governed by an intricate transcriptional network.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations